PRIORITIZATION OF TELECOMMUNICATION PROJECTS: DECISION ANALYSIS USING THE PROMÉTHÉE V METHOD - Gomes, Luiz Flavio Autran Monteiro; Rangel, Luis Alberto Duncan; Resende, Ricardo de Castro (Revista Economia & Gestão, 2015)
This article presents an application of the multicriteria method PROMÉTHÉE V to the problem of prioritizing telecommunication projects. The study was conducted inside of a major telecommunications company in Brazil. The adherence to a multicriteria approach allowed for taking into consideration technical as well as non technical evaluation criteria. Using PROMÉTHÉE V was particularly appropriate not only because the method performed an initial ranking of the set of projects, but also because it led to a constrained optimization of the obtained selection. It is then concluded that the application of PROMÉTHÉE V to the problem in question achieved its key purpose in the sense of organizing and solving a complex process of decision analysis. It also provided for interactivity during the analysis and useful simulations, giving transparency to the analysis and thus providing for a common base of understanding for all involved.